Effects of modern military backpack loads on walking speed and cardiometabolic responses of US Army Soldiers. (July 2021) - Looney, David P.; Doughty, Elizabeth M.; Figueiredo, Peter S.; Vangala, Sai V.; Pryor, J. Luke; Santee, William R.; McClung, Holly L.; Potter, Adam W.
Abstract: Introduction: Military leaders must understand how modern military equipment loads affect trade-offs between movement speed and physiological strain to optimize pacing strategies. Purpose: To evaluate the effects of load carried in a recently developed military backpack on the walking speed and cardiometabolic responses of dismounted warfighters. Methods: Fifteen soldiers (1 woman, 14 men; age, 22 ± 2 years; height, 173 ± 7 cm; body mass (BM), 73 ± 10 kg) completed incremental walking tests with four external load conditions (0, 22, 44, or 66% BM) using the US Army's newest backpack: the Modular Lightweight Load-Carrying Equipment 4000 (MOLLE 4000). Oxygen uptake (V̇O2 ) and heart rate (HR) were evaluated relative to maximal values (V̇O2max and HRmax respectively). Testing ceased when participants completed the highest tested speed (1.97 m s −1 ), exceeded a respiratory exchange ratio (RER) of 1.00, or reached volitional exhaustion. Results: Peak speed significantly decreased (p < 0.03) with successively heavier loads (0% BM, 1.95 ± 0.06 m s −1 ; 22% BM, 1.87 ± 0.10 m s −1 ; 44% BM, 1.69 ± 0.13 m s −1 ; 66% BM, 1.48 ± 0.13 m s −1 ). Peak V̇O2 was significantly lower (p < 0.01) with 0% BM (47 ± 5% V̇O2max ) than each load (22% BM, 58 ± 8% V̇O2max ; 44% BM, 63 ± 10% V̇O2max ; 66% BM, 61 ± 11% V̇O2max ). Peak HR was significantly lower (p < 0.01) with 0% BM (71 ± 5% HRmax ) versus each load (22% BM, 83 ± 6% HRmax ; 44% BM, 87 ± 6% HRmax ; 66% BM, 88 ± 6% HRmax ). Conclusion: Overburdened warfighters suffer severe impairments in walking speed even when carrying recently developed military load carriage equipment. Our results suggest that the relative work intensity of heavy load carriage may be better described when expressed relative to HRmax versus V̇O2max . Highlights: First physiological study on the U.S. Army's newest backpack: the MOLLE 4000. Makes evident heavier loads greatly reduce walking speed even when carried in ergonomic backpacks. Shows loading causes disproportionate increases in oxygen uptake and heart rate. Demonstrates heart rate is a better work intensity indicator of load carriage than oxygen uptake.